BUSINESS PLAN ANALYSIS OF HEALTHYLE - Ramadhani, Siti Aulia; Aziz, Fauzan; Arief, Mochammad Muminto (Moestopo International Review on Social, Humanities, and Sciences, 2024)
Catfish is a popular and affordable fishery product enjoyed by many. Healthyle, which stands for Healthy Lele, was established in 2023 to sell instant frozen catfish products, including ready-to-fry catfish and catfish katsu. These products are made from catfish farmed according to Good Fish Farming Practices (CBIB) and are halal certified. The catfish farming operation began in 2021. This study aims to analyzing Healthyle's marketing and operational strategies. This research uses data collection techniques carried out is secondary data. The result of this study is Healthyle's business plan highlights the need for comprehensive analysis to refine marketing and operational strategies. Despite a broad market for catfish in Jabodetabek and West Java, Healthyle’s marketing remains traditional and underutilized. The pricing is competitive, and the supply chain for raw materials is secure, suggesting that enhancing marketing efforts could significantly improve sales performance.